2014
DOI: 10.4103/0973-1482.136024
|View full text |Cite
|
Sign up to set email alerts
|

Primary extranodal non-Hodgkin′s lymphoma of oral cavity - A single centre retrospective study

Abstract: Involvement of oral cavity by lymphoma is rare. Plasmablastic lymphoma was the most common oral cavity NHL in our patients. Although number of cases in present study was less, our data suggests that oral NHL has aggressive course with less favorable outcome. Further large sample studies incorporating rituximab-based chemotherapy and more aggressive chemotherapy for plasmablastic lymphoma will be helpful for better understanding of treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Studies on the survival time for patients with DLBCL in the head and neck are controversial [24,36,37]; here, we added that lymphoma arising from the base of the tongue has a good prognosis. Lopez-Guillermo et al [36] showed that patients with DLBCL located on Waldeyer's ring (base of the tongue) often have a better prognosis than nodal DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the survival time for patients with DLBCL in the head and neck are controversial [24,36,37]; here, we added that lymphoma arising from the base of the tongue has a good prognosis. Lopez-Guillermo et al [36] showed that patients with DLBCL located on Waldeyer's ring (base of the tongue) often have a better prognosis than nodal DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of oral lymphomas can be challenging because there is low clinical suspicion, leading to diagnostic errors and delayed treatment. 9 A careful assessment, knowledge about HIV infection and its oral manifestations will help correctly and promptly diagnosing malignant lesions, avoiding situations such as in our case, where the initial diagnosis was of a dental infection.…”
Section: Discussionmentioning
confidence: 72%
“…Local volume increase, elastic-like mass formation, ulcerations, dental mobility, skin lesions and pain are often reported as symptoms in cases of Non-Hodgkin's Lymphoma in the oral cavity [14,15]. These clinical features may be confused with the clinical presentation of oral plasmacytoma, as can be observed in the case in question, then diagnosis of these conditions can be challenging, and when not done according to the recommended methods, can lead to errors and delays in the beginning of treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment of neoplasia belongs to hematologists and oncologists, the dental surgeon plays a fundamental role in the diagnosis of oral cavity lesions [13]. Therefore, well-founded doubts are essential to the diagnosis of oral plasmacytoma, avoiding delays in the diagnostic procedure that consequently lead to a decrease in survival rates [15].…”
Section: Discussionmentioning
confidence: 99%